Determinantes da distância percorrida no teste de caminhada de seis minutos em pacientes submetidos à cirurgia cardíaca - Oliveira, Géssica Uruga (2014)
Introduction: The walk test (6MWT) is a measure of functional capacity, simple, objective and reproducible, in which patients were instructed to walk as far as possible in six minutes. The 6MWT is widely used in cardiac rehabilitation as an indicator of functional status and as an outcome measure in patients after cardiac surgery, acute myocardial infarction and patients with chronic heart failure. Objective: The aim of this study was to identify the determinants of distance walked in six-minute walk test (6MWT) in patients undergoing cardiac surgery and establishing a reference equation and test its reliability. Methods: This is a descriptive study, sixty patients undergoing elective cardiac surgery type were evaluated. The assessment was performed preoperatively and at discharge. Were collected from medical records type of surgery , duration of mechanical ventilation, duration of cardiopulmonary bypass (CPB), days of ICU stay , days of hospitalization, ejection fraction of the left ventricle, hemoglobin and comorbidities (hypertension, diabetes and dyslipidemia). To assess functional capacity Functional Independence Measure (FIM) was applied, the quality of life was assessed using the Nottingham Health Profile (NHP). The 6MWT was performed at discharge. We used univariate analysis to select the variables to be used in the multivariate analysis model. For univariate analysis, we consider a level of significance less than 20% (P<0.20). Then the multivariate analysis was performed using multiple linear regression. For multivariate analysis, we consider a level of significance less than 5% (P<0.05). Results: The 6MWT was well tolerated by all patients and no test was interrupted before completing 6 minutes. The mean 6MWD was 260.20±89.20 meters. In multivariate analysis the following variables were selected: type of surgery (P=0.001), duration of cardiopulmonary bypass (CPB) (P=0.001), Functional Independence Measure - FIM (0.004) and body mass index - BMI (0.007) with r=0.91 and r2=0.83 with P<0.001. The equation derived from multivariate analysis: 6MWD = Surgery (89.42) + CPB (1.60) + MIF (2.79 ) - BMI (7.53) - 127.90. Conclusion: In this study, the determinants of 6MWD in patients undergoing cardiac surgery were: the type of surgery, CPB time, Functional Independence Measure and body mass index. It was possible in this study to generate a predictive equation for the DTC at discharge in patients undergoing elective cardiac surgery.